Different subtypes of motor cortex pyramidal tract neurons projects to red and pontine nuclei - Lopez-Virgen, Veronica; Olivares-Moreno, Rafael; de Lafuente, Victor; Concha, Luis; Rojas-Piloni, Gerardo (Frontiers in Cellular Neuroscience, 2022)
Pyramidal tract neurons (PTNs) are fundamental elements for motor control. However, it is largely unknown if PTNs are segregated into different subtypes with distinct characteristics. Using anatomical and electrophysiological tools, we analyzed in mice motor cortex PTNs projecting to red and pontine midbrain nuclei, which are important hubs connecting cerebral cortex and cerebellum playing a critical role in the regulation of movement. We reveal that the vast majority of M1 neurons projecting to the red and pontine nuclei constitutes different populations. Corticopontine neurons have higher conduction velocities and morphologically, a most homogeneous dendritic and spine distributions along cortical layers. The results indicate that cortical neurons projecting to the red and pontine nuclei constitute distinct anatomical and functional pathways which may contribute differently to sensorimotor integration.